Participation citoyenne et lutte contre la corruption - Ping Huang (Netcom)
This article addresses the issue of the Chinese citizens’ movements using digital social media as a means of action to fight against corruption, in the social-economical landscape of current China, which is undergoing significant transformations. We seek to identify the factors and processes of these movements and their effects on the relationship between governments and the citizens, as well as their impact on political decisions. Though our presented analysis of case studies highlights the potential of these digital networks as an effective tool for citizen mobilization and participation in the country, and an unquestionable improvement of government /citizens’ interactions, we emphasize the limitations to the Chinese cyber-movement, taking into account political factors and internal resistance from interest groups.